2022
DOI: 10.1097/pap.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

The Histologic Diversity of Chromophobe Renal Cell Carcinoma With Emphasis on Challenges Encountered in Daily Practice

Abstract: Chromophobe renal cell carcinoma (ChRCC) is the third most common renal cell carcinoma in adults. The aim of this review is to provide a comprehensive overview highlighting the broad morphologic spectrum of ChRCC, and offer a practical approach for handling cases in daily practice. For the purpose of this review, we classify ChRCC subtypes as (1) classic, (2) eosinophilic, (3) sarcomatoid, and (4) other rare patterns. The concept of eosinophilic ChRCC has significantly evolved, yet it still is one of the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
(205 reference statements)
0
5
0
Order By: Relevance
“…1A, B). 10 None of the 5 chromophobe RCCs were associated with tumor necrosis or sarcomatoid differentiation. All papillary RCCs were encapsulated and 1 of 4 tumors (patient #6) showed the historical “type 1” morphology, additionally with the architectural pattern recently described as “microcystic” (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…1A, B). 10 None of the 5 chromophobe RCCs were associated with tumor necrosis or sarcomatoid differentiation. All papillary RCCs were encapsulated and 1 of 4 tumors (patient #6) showed the historical “type 1” morphology, additionally with the architectural pattern recently described as “microcystic” (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…5,6 Of note, 4 of 5 chromophobe RCCs in our study showed classic chromophobe morphology including large polygonal cells with distinct cell borders (leaf/plant-like), smaller cells with eosinophilic cytoplasm, wrinkled irregular hyperchromatic nuclei (raisinoid), and perinuclear halos. 10 The fifth was a "multicystic pigmented" chromophobe RCC, a pattern with variably cystic to cribriform architecture and both intracytoplasmic and extracellular pigment, unique histologic findings that do not impact expected clinical behavior. 10,28 The genomic landscape of chromophobe RCC is complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, there were also a number invited review articles on various renal tumor topics by some of the speakers of the most recent 2021 KTF on various renal tumor entities. [27][28][29][30] It is worth noting that the 2 GUPS critical review articles of the recent advances in renal neoplasia, led by Ondřej and other colleagues, paved the road for the 2022 WHO blue book. 31,32 Throughout its 15-year history, Ondřej Hes personally organized both scientific and social programs and he always stated "KTF would not have been possible without the generous support of friends, colleagues, as well as the Biopticka laboratory and its staff, in particular Irena Kratochvílová and David Michal."…”
mentioning
confidence: 99%
“…Of note, there were also a number invited review articles on various renal tumor topics by some of the speakers of the most recent 2021 KTF on various renal tumor entities. 2730 It is worth noting that the 2 GUPS critical review articles of the recent advances in renal neoplasia, led by Ondřej and other colleagues, paved the road for the 2022 WHO blue book. 31,32…”
mentioning
confidence: 99%